2008
DOI: 10.1111/j.1469-0691.2008.01987.x
|View full text |Cite
|
Sign up to set email alerts
|

Viral respiratory infections at the Hajj: comparison between UK and Saudi pilgrims

Abstract: A high incidence of respiratory infection, including influenza, has been reported at the Hajj in Mecca, Saudi Arabia. Reported rates of influenza have been higher among UK than among domestic pilgrims, but this could be explained by methodological differences among studies. Accordingly, the present study compared the frequencies of respiratory viruses among UK and Saudi pilgrims using the same study design. Pilgrims with upper respiratory tract symptoms were recruited from Mecca and the neighbouring valley Min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
86
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(93 citation statements)
references
References 25 publications
5
86
1
1
Order By: Relevance
“…As the 2013 Hajj took place in midOctober none of the pilgrims in the French cohort reported receiving the vaccine of that season, however 44.2% reported receiving the vaccine in the previous northern winter season [44]. Among UK pilgrims, three studies reported the uptake between [22,32,33]. The latter compared the data between British and Saudi pilgrims with a reported uptake of 55% among 'at risk' and 29% among 'not at risk' UK pilgrims [32].…”
Section: Influenza Vaccine Uptakementioning
confidence: 89%
See 3 more Smart Citations
“…As the 2013 Hajj took place in midOctober none of the pilgrims in the French cohort reported receiving the vaccine of that season, however 44.2% reported receiving the vaccine in the previous northern winter season [44]. Among UK pilgrims, three studies reported the uptake between [22,32,33]. The latter compared the data between British and Saudi pilgrims with a reported uptake of 55% among 'at risk' and 29% among 'not at risk' UK pilgrims [32].…”
Section: Influenza Vaccine Uptakementioning
confidence: 89%
“…In 1998 and M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 9 conducted in Mina (Mecca) reporting a vaccine uptake of 4.4% among international and local pilgrims [18]. In 2006, a comparative study between the UK and Saudi Arabian pilgrims reported uptake of influenza vaccine among Saudi pilgrims of only 4%, compared to the uptake among UK pilgrims of 37% [32].…”
Section: Influenza Vaccine Uptakementioning
confidence: 97%
See 2 more Smart Citations
“…diarrhea, food poisoning, etc. are examples of communicable diseases [10,11,12,13]. Due to the physical exertion and overcrowding situation, some pre-existing chronic diseases such as asthma, heart disease, chronic chest conditions, diabetes, renal and liver disease may become harmful for pilgrims especially elderly which eventually favors the spread of communicable namely non-chronic diseases or infectious disease [14].…”
Section: Introductionmentioning
confidence: 99%